KONFLIK DAN KOMPROMI PASCA PILPRES 2024: SEBUAH TINJAUAN LITERATUR - Agus Setio Widodo; Diryo Suparto; Muhammad Marsa Syauqi; Fadhil Akmal Sailan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The 2024 Presidential Election (Pilpres) in Indonesia presented complex political dynamics, characterized by the emergence of political conflicts, social polarization, and various forms of compromise among political actors following the announcement of the election results. This article aims to analyze the forms, underlying factors, and implications of political conflict and compromise post-2024 Presidential Election through a literature review approach. The method used is a literature study examining various scientific sources, books, journal articles, research reports, and relevant publications regarding political conflict, reconciliation, governing coalitions, and democratic consolidation in Indonesia.The findings indicate that post-presidential election conflicts were driven not only by differing political preferences, but also by identity polarization, elite contestation, and evolving narratives on digital media. On the other hand, various forms of political compromise—including the formation of governing coalitions and inter-elite reconciliation—played a crucial role in maintaining political stability and ensuring governmental continuity. However, compromises predominantly oriented toward elite interests have the potential to undermine the effectiveness of opposition functions and the overall quality of democracy if not balanced by adequate accountability mechanisms. Therefore, strengthening democratic institutions, enhancing public political literacy, and securing the commitment of all stakeholders to prioritize conflict resolution through democratic mechanisms are essential. This study is expected to contribute to the development of Indonesian political studies, particularly regarding the dynamics of conflict and compromise in the post-2024 Presidential Election democratic system.